PERLAWANAN BAGUS RANGIN: PERANG NASIONAL YANG TERLUPAKAN - Herni Purnaningsih; Agus Mulyana (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2017)
This article entitled “Bagus Rangin Resistance: The Forgotten National War”. The main issue discussed in this essay is “Why there is resistance of Bagus Rangin in the year of 1806-1812 and how it affects society in the future”. The problem is assesed using the historical method through four steps of activity, there are; heuristic, criticism, interpretation and historiography. The result showed that the background of the Bagus Rangin resistance in 1806-1812 are because the high tax system applied by the colonial government, colonial exploitation and political domination of the Sultante of Cirebon which cause a reduction in the role of the Sultan in Cirebon residency. The leader of this resistance movement was called Bagus Rangin, people assumed that he is the messiah that being perceived as ‘Ratu Adil’ who will save the people, especially farmers and students from colonial tyranny. The impact of Bagus Rangin resistance is giving inspiration for the people of Cirebon to fight colonialism.